The Construction of romantic love as seen in Papemelroti Love and marriage greeting cards a Mmultimodal discourse analysis - Jogno, Diane Erica C.; Llenado, Camille S.; Vitorio, Raymund Victor M. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2011)
Greeting cards communicate reality in that they are reflective of a certain society's norms, conventions, beliefs, and attitudes toward a certain concept. They are also an avenue in which construction of a particular concept can be understood through an analysis of the different devices used in greeting cards. Therefore, this study seeks to determine how romantic love is constructed in the Papemelroti Love and Marriage greeting cards through a simultaneous analysis of linguistic and non-linguistic elements employed in such data. Using Kress and Van Leeuwen's Multimodal Discourse Analysis and Principle of Composition, this thesis takes into account a simultaneous analysis of the different elements present in the greeting cards so as to achieve an understanding of how romantic love is constructed in the said data. This particular research takes on a qualitative stance. It includes a description of the data and a multimodal analysis through the four strata of discourse, design, production, and distribution. Accordingly, different principles of composition will be applied to facilitate the understanding of the relationship among the elements present in the greeting cards. The findings suggest that the construction of romantic love in the greeting cards echoes that of the arguments of previous literature on the said concept. With the abundance of the you as well as the implications of a you, it is thus concluded that there is high regard for the beloved. There is also a noticeable wanting or desire to form a we with the beloved, though this may not be as evident as the regard for the beloved. Accodingly, there are also representations of intimacy which contribute to the construction of romantic love. Nevertheless, there are also particular elements in the data which accounted for the cultural variations preset in the representations of romantic love in the data, comprising a construction of romantic love as situated in the Philippine setting.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.